The ACCOBAMS survey initiative: the first synoptic assessment of cetacean abundance in the Mediterranean Sea through aerial surveys - Panigada, Simone; Pierantonio, Nino; Araújo, Hélder; David, Léa; Di-Méglio, Nathalie; Dorémus, Ghislain; Gonzalvo, Joan; Holcer, Draško; Laran, Sophie; Lauriano, Giancarlo; Paiu, Romulus-Marian; Perri, Morgane; et al. (Frontiers in Marine Science, 2024)
The “ACCOBAMS Survey Initiative” (ASI) is a pilot programme aimed at establishing an integrated and coordinated monitoring system for cetaceans across the Agreement on the Conservation of Cetaceans of the Black Sea, Mediterranean Sea and contiguous Atlantic (hereafter “ACCOBAMS”) area. Conducted in coordination with Mediterranean coastal countries, it supports the implementation of European and regional policies, in particular the EU Marine Strategy Framework Directive and the Ecosystem Approach process. In summer 2018, a synoptic survey was conducted across the Mediterranean Sea and contiguous Atlantic area, combining visual monitoring from aircrafts with visual and passive acoustic monitoring from vessels. Species density and abundance were estimated through design-based approach in a line-transect sampling framework. Based on data arising from the aerial survey only, uncorrected design-based abundance was obtained for striped (N=426,744, CV=0.13), common (N=65,359, CV=0.4), bottlenose (N=63,333, CV=0.17), and Risso´s dolphins (N=26,006, CV=0.3), Cuvier’s beaked whales (N=2,929, CV=0.4) and long-finned pilot whales (N=5,540 CV=0.4). A merged category of either striped or common dolphins resulted in 212,828 individuals (CV=0.26). Fin whales abundance of 1,749 animals (CV=0.3) was corrected for both availability and perception biases and resulted in 3,282 (CV=0.31). The ASI survey offers an overall picture of the distribution and abundance of cetaceans throughout the Mediterranean basin, providing robust estimates to be considered as a baseline for future regional systematic monitoring programmes. The ASI survey is the first step towards establishing a long-term monitoring program across the entire ACCOBAMS area, and, as such, it sets the basis for further future basin-wide monitoring efforts using systematic, shared, coordinated and comparable methods. The information gathered will further enhance knowledge on cetacean status, facilitating the development of informed conservation and mitigation measures, as well as supporting the implementation of international obligations. Furthermore, the outcomes of this survey will support both place- and threat-based conservation efforts in the ACCOBAMS area, through the identification of Important Marine Mammal Areas and Cetacean Critical Habitats. Here the results of the ASI survey are presented and discussed alongside proposed management and conservation actions aimed at ensuring the persistence of cetacean populations in the region.